Back Cover: Probing Proximity‐Tailored High Spin–Orbit Coupling in 2D Materials (Adv. Quantum Technol. 9/2020). Issue 9 (15th September 2020) - Sahoo, Krishna Rani; Chakravarthy, T. Pradeep; Sharma, Rahul; Bawari, Sumit; Mundlia, Suman; Sasmal, Satyaki; Raman, Karthik V.; Narayanan, Tharangattu N.; Viswanathan, Nirmal K.
Abstract : Simultaneous extraction of the magnetic and spin‐orbit coupling (SOC) information of an interface using the weak measurement assisted spin‐Hall effect of light (SHEL) is demonstrated as a novel probe to characterize materials' magnetic properties, see article number 2000042 by Karthik V. Raman, Tharangattu N. Narayanan, Nirmal K. Viswanathan, and co‐workers. A heterostructure of Fe and MoS2 monolayers is shown for enhanced SOC due to the proximity effect, which is proven via SHEL method and then confirmed using magneto‐optic Kerr effect (MOKE) studies.